Continuance Intention Use E-Filing : The Influence Quality Information, System, Service and Satisfaction as a Mediator - Benita Herliana Maharani; Bima Cinintya Pratama; Azmi Fitriati; Siti Nur Azizah (Jurnal Proaksi, 2023)
Satisfaction with the use of the e-filing system can be used as a basis for users to continue to have the intention to use the system. Because if users are satisfied with the e-filing system, there is a strong possibility that they will continue to use the system. The aim of this research is to examine the role of information, system and service quality in influencing continued intention to use e-filing. Apart from that, this research also aims to test the role of satisfaction as a mediator between these factors on the intention to continue using e-filing. The population of this research is users of the E-Filing system for individual taxpayers at the Purwokerto Pratama Tax Service Office with a sample of 200 respondents. Research analysis was carried out using structural equation modeling (SEM) with a Partial Least Square (PLS) approach. The results of this research show that the variables of information, system, and service quality have a positive effect on continuance intention. This research also shows that the satisfaction variable mediates the relationship between information, system and service quality on continuance intention.